Synthesis and characterization of an Fe-MOF@Fe3O4 nanocatalyst and its application as an organic nanocatalyst for one-pot synthesis of dihydropyrano[2,3-c]chromenes - Sheikhhosseini, Enayatollah; Yahyazadehfar, Mahdieh (Frontiers in Chemistry, 2023)
In this study, the recyclable heterogeneous cluster bud Fe-MOF@Fe3O4 ‘nanoflower’ composite (CB Fe-MOF@Fe3O4 NFC) was successfully synthesized using Fe(NO3)3·9H2O, 8-hydroxyquinoline sulfate monohydrate, and Fe3O4 nanoparticles by microwave irradiation. The as-prepared CB Fe-MOF@Fe3O4 NFC was characterized by X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDX), vibrational sampling magnetometry (VSM), and Fourier transform infrared spectroscopy (FTIR). The CB Fe-MOF@Fe3O4 NFC samples proved to have excellent catalytic activity. The activity of the CB Fe-MOF@Fe3O4 NFC nanocatalyst was explored in the synthesis of dihydropyrano[3, 2-c]chromene derivatives via a three-component reaction of 4-hydroxycoumarin, malononitrile, and a wide range of aromatic aldehyde compounds. Optimized reaction conditions had several advantages, including the use of water as a green solvent, environmental compatibility, simple work-up, reusability of the catalyst, low catalyst loading, faster reaction time, and higher yields.